Karel, Jarda und das wahre Leben - Och, Sheila 1940-1999 (Arena-Verl., 1998)
In the period following the collapse of Communism during the Velvet Revolution of 1989-90, two twelve-year-old Prague boys pursue their dreams of a Western life by attempting to become rich.
Keywords: Geschichte 1995; Kind; Alltag, Brauchtum; Moneymaking projects -- Fiction; Urgroßvater; Kapitalismus; Geld; Jugend; Familienkonflikt; Junge; Freundschaft; Samtene Revolution; Marktwirtschaft; Wirtschaftssystem; Tschechische Republik; Prague (Czech Republic) -- Social life and customs -- Fiction; Tschechien; Prag; Jugendbuch; Kinderbuch; Literatur